Elemental Chlorine-Free Bleaching of Soda Rapeseed Pulp - Potůček, František; Říhová, Martina (Česká společnost průmyslové chemie, 2016)
Soda pulp cooked from rapeseed straw (Brassica napus L. convar. napus, in our case winter line genotype Labrador) was subjected to a four-stage elemental chlorine-free bleaching under laboratory conditions. Chlorine dioxide and hydrogen peroxide were used as bleaching chemicals. For comparison, kraft pulp cooked from a blend of spruce and pine was subjected to the same bleaching sequence D0 EP D1 P. The initial kappa number of both pulps was 18.8. After each bleaching step, the optical and strength properties were measured. The preliminary results showed that bleachability of soda rapeseed pulp was lower in comparison with kraft softwood pulp for D0EPD1P bleaching sequence. The brightness increment of 43.2 % ISO and 48.5 % ISO was achieved for soda and kraft pulps, respectively. However, the bleaching had a negative impact on the zero-span breaking length which decreased from 3.9 km for unbleached soda pulp to 3.6 km for bleached soda pulp.
Bělení natronové řepkové buničiny bez elementárního chloru
Keywords: soda rapeseed pulp; ECF bleaching; brightness; zero-span breaking length; natronová řepková buničina; ECF bělení; bělost; tržná délka vláken